1989
DOI: 10.1111/j.1464-410x.1989.tb05942.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Human Prostatic Adrenoceptors using Pharmacology Receptor Binding and Localisation

Abstract: Benign prostatic enlargement is a common cause of bladder outlet obstruction. Recent work has demonstrated the important role played by the sympathetic nervous system in the control of prostatic muscle tone. Although isometric muscle strip studies and clinical trials have highlighted the influence of alpha-1 adrenoceptors, radioisotope ligand binding studies have demonstrated a relatively increased density of alpha-2 adrenoceptors in the muscle within prostatic tissue, the significance of which is as yet unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
2

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 26 publications
3
84
0
2
Order By: Relevance
“…8 Human prostatic tissue also responds to the addition of ␣ 1 -adrenoceptor agonists with contractions 9 that are blocked by subtype-selective ␣ 1 -adrenoceptor antagonists. 10 Consistent with this finding is evidence that ␣ 1A ( ␣ 1c -)-adrenoceptors predominate in this tissue. 11 ␣ -Adrenoceptor-mediated contractions are also inhibited by pertussis toxin and are sensitive to (L-type) Ca 2+ channel blockers.…”
Section: Human Prostate Innervation and Contractilitysupporting
confidence: 77%
“…8 Human prostatic tissue also responds to the addition of ␣ 1 -adrenoceptor agonists with contractions 9 that are blocked by subtype-selective ␣ 1 -adrenoceptor antagonists. 10 Consistent with this finding is evidence that ␣ 1A ( ␣ 1c -)-adrenoceptors predominate in this tissue. 11 ␣ -Adrenoceptor-mediated contractions are also inhibited by pertussis toxin and are sensitive to (L-type) Ca 2+ channel blockers.…”
Section: Human Prostate Innervation and Contractilitysupporting
confidence: 77%
“…bunazosin is a potent postsynaptic al-blocker with a higher selectivity than that of prazosin (13,14), [3H]-bunazosin should also be a useful ligand for binding assays (3,13,14). The al-adrenoceptors in the prostate were reported to be localized in the stroma by Chappel et al (2) and James et al (4). Our previous study (6,12) demonstrated the approximate localization of aladrenoceptors in the human prostate using [3H]-prazosin and [125I]-HEAT.…”
Section: Whenmentioning
confidence: 99%
“…Recent research on adrenoceptors in the human prostate has mainly been performed using binding assays and in vitro receptor autoradiography, which has demonstrated that both [3H]-prazosin and [1251]_ iodo-2-[8-(4-hydroxyphenyl)-ethylaminomethyl] tetralone ([125I]-HEAT) bind specifically to the a1-adrenoceptors (2,4,10,11). We have also reported on the density and localization of a1-receptors in the hypertrophic prostate using the same ligands (6,12).…”
mentioning
confidence: 99%
“…Prostat dokusunda hem alfa-l reseptörlerin hemde alfa-2 reseptörlerin bulunmasına karşın düz kasların kasılmasında alfa-l reseptörlerin sorumlu olduğu, alfa-2 reseptörlerin ise özellikle nor-adrenalin salgılanmasını kontrol eden feedback mekanizmasında rol oynadığı bilinmektedir (13,14,15). Selektif alfa-l blokörlerinin kullanımı ise, prazosin ile yapılan deneylerden sonra yaygınlaşmıştır.…”
Section: T Ta Ar Rt Tı ış şM Ma Aunclassified